Differences in the Level of Career Aspirations of High School Students with Minangkabau and Chinese Cultural Backgrounds - Ghenong, Hildagardis Oje; Nirwana, Herman; Kiram, Yanuar (Jurnal Aplikasi IPTEK Indonesia, 2021)
Career aspiration is one of the factors that influence one's career maturity. Career aspirations direct individual behavior to achieve the career that is their hopes or dreams. Career aspirations can help students choose a secondary school that matches the abilities and potentials of the individual. The purpose of this study was to analyze the differences in career aspirations of high school students with Minangkabau and Chinese cultural backgrounds. This research uses a comparative descriptive quantitative approach. The population in this study were students of class XI and XII who have Minangkabau and Chinese cultural backgrounds at SMA Negeri 1 Padang and SMA Don Bosco Padang. The research sample was 295 students consisting of 173 Minangkabau students (79 male & 94 female) and 122 Chinese students (64 male and 58 female). The instrument used was the Career Aspiration Level Entry List (DITAK). The measuring instrument used is valid and the reliability coefficient of DITAK is 0.86. Based on the results of the study, there are differences in the level of career aspirations of high school students with Minangkabau and Chinese cultural backgrounds, where the level of career aspirations of Chinese students is higher than that of Minangkabau students. The implication of the results of this study is as discussion material and input for the school in making guidance and counseling service programs, especially in the field of career development.